2018
DOI: 10.1007/s00029-018-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Transition formulas for involution Schubert polynomials

Abstract: The orbits of the orthogonal and symplectic groups on the flag variety are in bijection, respectively, with the involutions and fixed-point-free involutions in the symmetric group S n . Wyser and Yong have described polynomial representatives for the cohomology classes of the closures of these orbits, which we denote asŜ y (to be called involution Schubert polynomials) andŜ FPF y (to be called fixed-point-free involution Schubert polynomials). Our main results are explicit formulas decomposing the product ofŜ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…Using this information, we prove that involutions inS n have what we call the Bruhat covering property:Theorem 1.1 (Bruhat covering property). If y ∈Ĩ n and t ∈S n is a reflection, then there exists at most one z ∈Ĩ n such that {wt : w ∈ A(y) and ℓ(wt) = ℓ(w) + 1} ∩ A(z) = ∅.The analogue of this result for involutions in S n was shown in [11], and served as a key lemma in proofs of "transition formulas" for certain involution Schubert polynomials. We conjecture that the same property holds for arbitrary Coxeter systems, in the following sense.Let (W, S) be a Coxeter system with length function ℓ : W → N and Demazure product • : W × W → W .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Using this information, we prove that involutions inS n have what we call the Bruhat covering property:Theorem 1.1 (Bruhat covering property). If y ∈Ĩ n and t ∈S n is a reflection, then there exists at most one z ∈Ĩ n such that {wt : w ∈ A(y) and ℓ(wt) = ℓ(w) + 1} ∩ A(z) = ∅.The analogue of this result for involutions in S n was shown in [11], and served as a key lemma in proofs of "transition formulas" for certain involution Schubert polynomials. We conjecture that the same property holds for arbitrary Coxeter systems, in the following sense.Let (W, S) be a Coxeter system with length function ℓ : W → N and Demazure product • : W × W → W .…”
mentioning
confidence: 90%
“…Can, Joyce, and Wyser's description of A(y) for y ∈ I n in [6] implies that w ∈ S n belongs to A(y) if and only if [w] E ∈ A([y] E ) for all subsets E ⊂ [n] which are invariant under y and contain at most two y-orbits; cf. [11,Corollary 3.19]. This "local" criterion for membership in A(y) was an important tool in the proofs of the main results in [11].…”
Section: Cycle Removal Processmentioning
confidence: 99%
See 1 more Smart Citation
“…For z ∈ F ∞ , define z * ∈ F ∞ by conjugating z by n · · · 321 where n ∈ 2N is minimal such that z(i) = i − (−1) i for all integers i > n; the map w 1 w 2 · · · w l → (n − w 1 )(n − w 2 ) · · · (n − w l ) is then a bijection H Sp (z) → H Sp (z * ). [8,10,11,12]. Setting β = 0 in GP λ , alternatively, yields the well-known Schur P -function P λ .…”
Section: ) =mentioning
confidence: 99%
“…Can, Wyser and the author [7] return to the study of the degenerate involution Schubert polynomial associated to the longest permutation viewed as a µ-involution and use geometric considerations to show that certain multiplicity-free sums of ordinary Schubert polynomials have very simple factorizations. Hamaker, Marberg and Pawlowski [16] have given a transition formula for involution Schubert polynomials, generalizing the transition formula for ordinary Schubert polynomials established by Lascoux and Schützenberger [19]. Hamaker, Marberg and Pawlowski [15] have also initiated a study of involution Stanley symmetric functions, a natural limit of involution Schubert polynomials, and shown that they can be expanded positively in the Schur P -basis; they have also established a similar result for fixed-point-free involution Stanley symmetric functions [13].…”
Section: Introductionmentioning
confidence: 99%